Efecto antibacteriano in vitro del aceite esencial de Citrus reticulata variedad Satsuma “mandarina” sobre Staphylococcus aureus y Escherichia coli - Velarde Salazar, Hernan Alonso (2017)
OBJECTIVE: Demonstrate the in vitro antibacterial effect of the essential oil of Citrus reticulata variety Satsuma "mandarin" on Staphylococcus aureus and Escherichia coli. MATERIAL AND METHOD: The steam distillation method was used to obtain the essential oil of Citrus reticulata Satsuma variety. The antibacterial effect on Staphylococcus aureus and Escherichia coli was determined by the disc diffusion method, using concentrations of 30.60 and 90% of essential oil, in addition to control drugs (Vancomycin and Ciprofloxacin). RESULTS: it was evidenced that at all concentrations of the essential oil there was an antibacterial effect, since the inhibition halos were greater than 8 mm according to Duraffourd scale, in addition to the higher concentration used the antibacterial effect is higher. There was a greater antibacterial effect on Staphylococcus aureus than on Escherichia coli. CONCLUSION: The essential oil of Citrus reticulata variety Satsuma "mandarin" has an antibacterial effect in vitro on Staphylococcus aureus and Escherichia coli.